(untitled) (Revista de História Regional, 2007)
This article analyses the intellectual trajectory, the ideas, and the eugenics propaganda developed by the physician and eugenicist, Renato Kehl, between the 1910´s and 1920s. The aim is to understand the development of the eugenics field and the social network established by this figure as a means of publicizing eugenics, in Brazil as well as in Latin America in general. This article analyses also how the concepts of eugenics are closely linked to those of social medicine, calling special attention to Renato Kehls proximity to intellectuals involved with the sanitarian movement and to the presuppositions originating in preventative eugenics.